2003
DOI: 10.1002/hlca.200390212
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of the Conversion of 2‐Phenoxyethanol into Phenol and Acetaldehyde by Acetobacterium sp.

Abstract: The conversion of 2‐phenoxyethanol to phenol and acetate by the anaerobic bacterium Acetobacterium sp. strain LuPhet1 proceeds through acetaldehyde with concomitant migration of a H‐atom from C(1) to C(2) of the glycolic moiety. Separate feeding experiments with (R)‐ and (S)‐2‐phenoxy(1‐2H)ethanol, prepared via chemoenzymatic syntheses, indicate that the H‐atom involved in the 1,2‐shift is the pro‐S one of the enantiotopic couple of the alcohol function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…3 This phenomenon was related to the loss of enzymatic activity when biomass is not exposed to this solvent. The same study proposed that the ether cleavage of M2P included the transhydroxylation reaction based on that reported by Speranza et al 22 It has also been reported that co-factor B 12, herein metabolized from CoCl 2 , could act as a catalyst of the transhydroxylation reaction of glycol ethers. 23 In this regard, EPS may have significant cobalt sorption capacity, 24 and it could play a key role in the bioavailability of this metal to bacteria.…”
Section: Flocculation Testmentioning
confidence: 79%
“…3 This phenomenon was related to the loss of enzymatic activity when biomass is not exposed to this solvent. The same study proposed that the ether cleavage of M2P included the transhydroxylation reaction based on that reported by Speranza et al 22 It has also been reported that co-factor B 12, herein metabolized from CoCl 2 , could act as a catalyst of the transhydroxylation reaction of glycol ethers. 23 In this regard, EPS may have significant cobalt sorption capacity, 24 and it could play a key role in the bioavailability of this metal to bacteria.…”
Section: Flocculation Testmentioning
confidence: 79%
“…17 However, the desired product could not be obtained using any of these routes. Ultimately, we were able to obtain the desired material in 88% yield through the mildly acidic deprotection of dimethyl acetal 15 with Amberlyst-15 resin, 39,40 although the material had to be stored at −20 °C at all times to prevent decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…However in two cases of eliminase-catalyzed radical reactions a complete exchange of the mobile H-atom has been observed [28,29]. The biodegradation of the ethanolamines described here appears to be similar to the conversion of 2-phenoxyethanol into acetate mediated by another strain of the anaerobic homoacetogenic bacterium Acetobacterium [30,31]. While adenosylcobalamin (coen- Fig.…”
Section: Resultsmentioning
confidence: 61%